Evaluation of specific personality characteristics in different physical disorders - Díaz A., Gloria (2007)
It identifies the determined contributions of the clinical investigation on characteristic of the personlaity in risk of physical disease, and that can sert evaluated by diagnosed instruments. It indicates certain conditions that the boarding for an integral understanding of the patient favors.